2021
DOI: 10.1080/21505594.2021.1897247
|View full text |Cite
|
Sign up to set email alerts
|

PE_PGRS3 ensures provision of the vital phospholipids cardiolipin and phosphatidylinositols by promoting the interaction betweenM. tuberculosisand host cells

Abstract: PE_PGRS proteins of Mycobacterium tuberculosis ( Mtb ) constitute a large family of complex modular proteins whose role is still unclear. Among those, we have previously shown, using the heterologous expression in Mycobacterium smegmatis , that PE_PGRS3 containing a unique arginine-rich C-terminal domain, promotes adhesion to host cells. In this study, we investigate the role of PE_PGRS3 and its C-terminal domain directly in Mtb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The protease domain of PE_PGRS35 localizes in the unique C-terminal domain that is positioned to recognize and cleave off the tubular-like PE domain (Fig 1A). ExperimentalAU : Pleasecheckifthechangesmadeinthes data indicate that cleavage of PE_PGRS proteins remove approximately 11 kDa fragment, corresponding to approximately 110 N-terminal amino acids [13,14], though the exact cleavage site has not yet been identified. These observations, together with the predicted structure of the PE_PGRSs (see below), suggest that cleavage of the PE domain may occur upstream the PGRS domain.…”
Section: The Predicted Structure Supports the Model Claiming Cleavage...mentioning
confidence: 99%
“…The protease domain of PE_PGRS35 localizes in the unique C-terminal domain that is positioned to recognize and cleave off the tubular-like PE domain (Fig 1A). ExperimentalAU : Pleasecheckifthechangesmadeinthes data indicate that cleavage of PE_PGRS proteins remove approximately 11 kDa fragment, corresponding to approximately 110 N-terminal amino acids [13,14], though the exact cleavage site has not yet been identified. These observations, together with the predicted structure of the PE_PGRSs (see below), suggest that cleavage of the PE domain may occur upstream the PGRS domain.…”
Section: The Predicted Structure Supports the Model Claiming Cleavage...mentioning
confidence: 99%
“…Furthermore, the authors suggested the involvement of PE_PGRS3 in scavenging lipids, which might be utilized as a carbon source by intracellularly located Mtb . Additionally, De Maio et al documented that the PE_PGRS3 protein, once translocated through the plasma membrane through an ESX5-dependent mechanism [ 57 , 58 ], remains associated with the mycobacterial membrane or may possibly be released to exert its activity and serve as a bridge between pathogen and the target host cells [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, macrophages exposed to GQDs increase the presence of phosphoglycerides, sphingolipids, and oxidized lipids ( Shao et al, 2023 ). While not completely elucidated, the role of host lipids and the changes associated with Mtb infection, play a key role in the pathogenesis of TB ( De Maio et al, 2021 ). Indeed, we have recently demonstrated that phosphoglycerides such as phosphorylated phosphatidylinositol (PtdIns), cardiolipin (CL), and phosphatidic acid (PA), were recognized by a surface protein of Mtb which appears to ensure phosphate acquisition from the environment and mediate adhesion to host cell.…”
Section: Discussionmentioning
confidence: 99%